2020
DOI: 10.1016/j.algal.2020.101960
|View full text |Cite
|
Sign up to set email alerts
|

Composition and rheological properties of microalgae suspensions: Impact of ultrasound processing

Abstract: In this study the rheological properties of aqueous suspensions of three microalgae species, Nannochloropsis gaditana, Scenedesmus almeriensis and Spirulina platensis, were investigated as a function of solids content, and related to their composition and microstructure. In addition, the impact of ultrasound processing on their structuring ability was also studied. The less rigid character of the Spirulina platensis cell walls (with very low carbohydrate contents) and the presence of extracellular components p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 86 publications
1
9
1
3
Order By: Relevance
“…This is in close agreement with the results reported by Parniakov et al [17] for Nannochloropsis spp., who found that the optimal extraction of the total phenolic compounds assisted by ultrasound (W= 400 W) was achieved after 15 min. Martínez-Sanz et al [31] also found a huge increase in the TPC extraction from Nannochloropsis gaditana, Scenedesmus almeriensis and Spirulina platensis after ultrasound treatment for 5 min. The temperature and pH did not significantly influence the polyphenol extraction (p = 0.5568 and 0.2021, respectively).…”
Section: Antioxidant Capacity and Compoundsmentioning
confidence: 91%
“…This is in close agreement with the results reported by Parniakov et al [17] for Nannochloropsis spp., who found that the optimal extraction of the total phenolic compounds assisted by ultrasound (W= 400 W) was achieved after 15 min. Martínez-Sanz et al [31] also found a huge increase in the TPC extraction from Nannochloropsis gaditana, Scenedesmus almeriensis and Spirulina platensis after ultrasound treatment for 5 min. The temperature and pH did not significantly influence the polyphenol extraction (p = 0.5568 and 0.2021, respectively).…”
Section: Antioxidant Capacity and Compoundsmentioning
confidence: 91%
“…Sonication had dissimilar effects dependent on the microalgal species, wherein increased antioxidant activity was reported for A. platensis but reduction for N. gaditana and S. almeriensis . 50 Antioxidant activities as impacted by HPH appear to be more differentiated by their ferric reducing capacities. The limited consequence of homogenising pressure on the microalgal digest suspensions was comparable for the DPPH radical scavenging activities and total phenolic contents.…”
Section: Resultsmentioning
confidence: 99%
“…32 Due to the antioxidant potential being linked to the presence of polyphenols and other bioactive compounds in a complex mechanism, a link between the antioxidant capacity of samples and the release or degradation of specific components could not be explicitly made. 50 Other variables that could influence the antioxidant capacities and radical scavenging activities of microalgae are solvent polarity and dose-dependency. 32,51–53…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae suspensions may present different rheological properties depending on the microalgae strains and its cell properties, such as cell wall composition and structure [98]; in this respect, downstream processing such as US can disrupt cells' clusters or promoting release of intracellular components changing the rheological properties of microalgae suspensions [99]. Bertsch et.…”
Section: Microalgae Proteinsmentioning
confidence: 99%